The Learning of Pancasila Values Construction Through Moral Inquiry: A Phenomenological Study of Prosocial Character of Health Vocational Students - Silmi Kapatan Inda Robby; Kama Abdul Hakam; Mupid Hidayat; Warlim Warlim (Newinera Publisher, 2026)
The pedagogical challenge in health vocational education lies in preventing the reduction of Civic Education to a mere formalistic exercise that fails to influence professional behavior. This study investigates the construction of Pancasila values through the implementation of Moral Inquiry as a deliberative instructional strategy designed to foster prosocial character among health vocational students. We explored the lived experiences of eight participants from Speech Therapy, Radiodiagnostic and Radiotherapy, and Hospital Administration programs who engaged in a systematic value internalisation process. By utilizing professional ethical dilemmas as the primary stimulus for cognitive disequilibrium, the research sought to move students beyond conventional rule-following toward a post-conventional civic disposition. Adopting a transcendental descriptive phenomenological approach, we focused on the structural and textural descriptions of the students' moral development. Our findings indicate that the construction of prosocial character is achieved through a rigorous process of ego reduction where the students’ self-oriented professional motives are surrendered to the civic imperatives of humanity and social justice. We identified a critical transition from theoretical value recognition to a habitual